2012
DOI: 10.1074/jbc.m111.244285
|View full text |Cite
|
Sign up to set email alerts
|

Islet Amyloid Polypeptide Triggers Limited Complement Activation and Binds Complement Inhibitor C4b-binding Protein, Which Enhances Fibril Formation

Abstract: Islet amyloid polypeptide (IAPP) is synthesized in pancreatic␤-cells and co-secreted with insulin. Aggregation and formation of IAPP-amyloid play a critical role in ␤-cell death in type 2 diabetic patients. Because A␤-fibrils in Alzheimer disease activate the complement system, we have here investigated specific interactions between IAPP and complement factors. IAPP fibrils triggered limited activation of complement in vitro, involving both the classical and the alternative pathways. Direct binding assays conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…Interestingly, genes up-regulated in brains of patients with late onset AD such as Tyrobp , Trem2 and C4b (Brouwers et al, 2012; McGeer et al, 1989; Zhang et al, 2013) were decreased in brains of Il10 deficient APP/PS1 mice. Along similar lines, previous studies have shown that TLR2 and C4b bind Aβ and trigger microglial activation (Richard et al, 2008) and Aβ fibril formation (Sjolander et al, 2012; Trouw et al, 2008), and APP/PS1 + Il10 −/− brains had decreased expression of both genes. Strikingly, Chakrabarty and coworkers have demonstrated that adeno-associated viral expression of Il10 in brains of APP transgenic mice leads to age-dependent up-regulation of Cxcl10 , Tlr2 , C4b and C3ar1 transcripts (Chakrabarty et al, 2015).…”
Section: Discussionsupporting
confidence: 78%
“…Interestingly, genes up-regulated in brains of patients with late onset AD such as Tyrobp , Trem2 and C4b (Brouwers et al, 2012; McGeer et al, 1989; Zhang et al, 2013) were decreased in brains of Il10 deficient APP/PS1 mice. Along similar lines, previous studies have shown that TLR2 and C4b bind Aβ and trigger microglial activation (Richard et al, 2008) and Aβ fibril formation (Sjolander et al, 2012; Trouw et al, 2008), and APP/PS1 + Il10 −/− brains had decreased expression of both genes. Strikingly, Chakrabarty and coworkers have demonstrated that adeno-associated viral expression of Il10 in brains of APP transgenic mice leads to age-dependent up-regulation of Cxcl10 , Tlr2 , C4b and C3ar1 transcripts (Chakrabarty et al, 2015).…”
Section: Discussionsupporting
confidence: 78%
“…A further hallmark of the islets in type 2 diabetic patients is the ectopic accumulation of extracellular amyloid fibrils, which is partially mediated by excess free fatty acids (FFA) and exerts cytotoxic effects on β-cells [31, 32]. Intriguingly, amyloid fibrils can trigger local complement activation via C1q [33, 34], thereby facilitating local inflammation and macrophage activation, ultimately promoting β-cell death. Nevertheless, immunohistology studies have shown that there is limited MAC deposition on the islets that colocalizes with amyloid polypeptide fibrils [34].…”
Section: ) the Role Of Complement In Physiology And Pathology Of Thementioning
confidence: 99%
“…Intriguingly, amyloid fibrils can trigger local complement activation via C1q [33, 34], thereby facilitating local inflammation and macrophage activation, ultimately promoting β-cell death. Nevertheless, immunohistology studies have shown that there is limited MAC deposition on the islets that colocalizes with amyloid polypeptide fibrils [34]. This limited MAC deposition could be attributed to the fact that amyloid fibrils interact with C4BP and fH, which inhibit complement activation[34].…”
Section: ) the Role Of Complement In Physiology And Pathology Of Thementioning
confidence: 99%
See 2 more Smart Citations